2001
DOI: 10.1212/wnl.56.10.1299
|View full text |Cite
|
Sign up to set email alerts
|

Fever in subarachnoid hemorrhage

Abstract: Fever in SAH is associated with vasospasm and poor outcome independently of hemorrhage severity or presence of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
4
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(145 citation statements)
references
References 31 publications
8
128
4
5
Order By: Relevance
“…Most studies of fever in patients with aSAH have addressed the incidence of fever throughout the ICU stay. 6,18 Fernandez et al 6 demonstrated that fever in aSAH, with an average temperature elevation of about 0.6°C ± 0.58°C, is seen as early as the first 24 hours of admission. These studies also suggest that in 91% of TBI patients 35 and 73% aSAH patients 18 staying in an ICU the development of fever may be explained by infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of fever in patients with aSAH have addressed the incidence of fever throughout the ICU stay. 6,18 Fernandez et al 6 demonstrated that fever in aSAH, with an average temperature elevation of about 0.6°C ± 0.58°C, is seen as early as the first 24 hours of admission. These studies also suggest that in 91% of TBI patients 35 and 73% aSAH patients 18 staying in an ICU the development of fever may be explained by infections.…”
Section: Discussionmentioning
confidence: 99%
“…6,18 Fernandez et al 6 demonstrated that fever in aSAH, with an average temperature elevation of about 0.6°C ± 0.58°C, is seen as early as the first 24 hours of admission. These studies also suggest that in 91% of TBI patients 35 and 73% aSAH patients 18 staying in an ICU the development of fever may be explained by infections. As infection or sepsis may be unlikely within the first 24 hours of ICU admission in patients with TBI or aSAH, it is possible that an early fever represents an acute response to injury or inflammation, or that it may be related to damage of thermoregulatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Family structure was recorded as living alone, living with a spouse only, or living with children. A complicating infection was defined as a body temperature 38.3°C for two or more consecutive days, based on a preceding study (Oliveira-Filho et al 2001). All patients were diagnosed using CT scan or MRI.…”
Section: Methodsmentioning
confidence: 99%
“…Fever has been associated with worse outcomes [123,124], so that the most recently published guidelines for SAH recommend aggressive treatment of fever to normothermia [125]. No clear evidence exists in using hypothermia after SAH.…”
Section: Subarachnoid Hemorrhagementioning
confidence: 99%